Safety and Efficacy of Unicondylar Knee Prosthesis Treatment for Unicompartmental Osteoarthritis of the Knee Joint. (15th July 2022) - Zhang, Dahua; Zhang, Xiang
Abstract : Background. Knee osteoarthritis (KOA) is a chronic disease that seriously endangers the health of the elderly. Choosing appropriate surgery for knee osteoarthritis patients is especially important. Objective . To investigate the safety and efficacy of unicondylar knee prosthesis treatment for unicompartmental osteoarthritis of the knee. Materials and Methods . One hundred patients with unicondylar osteoarthritis of the knee treated in our hospital from June 2019 to June 2021 were selected as retrospective study subjects and were divided into 50 cases each in the comparison group and the observation group according to the different surgical methods. Among them, the comparison group was treated with unicondylar knee arthroplasty (UKA), and the observation group was treated with unicondylar knee prosthesis replacement, and the differences in AKS score, knee flexion angle, tibial angle orthosis, joint mobility, and postoperative recovery were compared between the two groups. Results . The AKS score and knee flexion angle score of the observation group were higher than those of the comparison group after surgery. However, the tibial angle orthopedic score of the observation group was significantly lower than that of the comparison group after surgery for comparison, and the VAS score of the observation group was lower than that of the comparison group. However, the Lysholm score of the observation group was higher than that of the control group after surgery (P < 0.05 ). The complication rate of patients in the observation group was significantly lower than that of the comparison group, and the HSS score, VAS score, and knee mobility (ROM) of the two groups were statistically significant (P < 0.05 ) when compared at 7 d after surgery and 6 months after surgery. Conclusion . The clinical efficacy of unicondylar knee prosthesis replacement for osteoarthritis of the knee is better than that of unicondylar knee arthroplasty (UKA) treatment.